Pengaruh Konsentrasi COD Terhadap Efektifitas Pengolahan Air Limbah Secara UASB - Endang Suryadi (Jurnal Kimia dan Kemasan, 1997)
A study on effect of various COD concentration of soy-bean sauce wasteweter treatment using UASB type bioreactor has been conducted. The result exhibited that over 90 % of the COD could be removed. Removal rate of COD was not significantly affected by elapsing time of the treatment and for flucatuating COD concentration, however, it appeared to poin out a significant difference as a result of increasing COD level of the feed solution. The higher the COD level was fed, the more the amount of COD was eliminated. The generated gas volume was also raised as the COD Concentration was increased.